On the bramble way to Mg metal anodes in secondary Mg ion batteries. (1st July 2023) - Zou, Guodong; Feng, Jiawen; Zhao, Xue; Wang, Jinming; Wang, Yangyang; Yang, Weihao; Wei, Mengyao; Wang, Yimin; Li, Lanjie; Ren, Liqun; Fernandez, Carlos; Peng, Qiuming
Highlights: Recent advances of Mg metal anodes in rechargeable Mg metal batteries (RMBs) are summarized. The roles and challenges of Mg metal anode in RMBs are discussed. Novel strategies of Mg metal anode modification (such as Mg alloys anode design, aqueous electrolyte optimization) are introduced. Prospects for the future development of high-performance Mg metal anode are provided. Abstract: As a prospective alternative to lithium-ion batteries, rechargeable magnesium metal batteries (RMBs) have many unparalleled advantages, including direct use of Mg metal as the electrode; large nature abundance; intrinsically safe merits; high theoretical volumetric capacity. Nonetheless, there exist a large number of challenges on electrodes for their applications. Among them, surface passivation, uneven deposition/dissolution, and corrosion are critical issues that severely hinder the development of Mg anodes in RMBs. This review gives a specific, comprehensive, and in-depth summary of mechanisms relative to these problems. Subsequently, it displays the protection progresses of the Mg metal anode via three-dimensional host nanostructure fabrication, Mg alloys anode design, current collector modification, artificial solid-electrolyte interphase construction, and electrolyte optimization. Finally, future perspectives and outlooks in developing the other blossom of these strategies for rechargeable Mg batteries are also discussed. This overview provides significant guidance for designing and fabricating high-performance Mg metal anodes in secondary Mg batteries and boosting their commercial applications.